Adaptation Patterns on Coastal Communities of the "Gopla" Forest Management Phenomenon at Tasikmadu Village, Trenggalek Regency - Normansyah Fuad; Keppi Sukesi; Edi Susilo (ECSOFiM (Economic and Social of Fisheries and Marine Journal), 2021)
Gopla is a coastal community adaptation phenomenon that occurs in the Prigi Beach Area which was pioneered by Mr. Paniyo (Gopla). This phenomenon is a change in deviant behavior where people use forest land that does not belong to them for personal gain. This adaptation is triggered by the increase in the necessities of life caused by the economic crisis and the reduction in basic income from the fisheries and agriculture sectors, which are his main livelihoods. This study has the objectives of 1) knowing the adaptation of coastal communities within the scope of community interaction with forest ecosystems, 2) formulating adaptation patterns that occur in these coastal communities. This study uses a qualitative method with a case study approach. From this research, it was found that the adaptation carried out in the community turned out to include adaptation to the ecosystem, socio-culture, and economic system which are interrelated.